Cope strategies for victims of sexual violence in adolescents: scoping review - Istiani Yoviana; Tetti Solehati; Dyah Setyorini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Sexual abuse that occurs during adolescence can affect its development in various aspects of life. The stressful situation experienced by the victim has an impact on the physiological, psychological, and social. Individuals will do coping to overcome them. Adolescents often fall into maladaptive coping strategies, causing them to experience depression. This study aims to identify coping strategies for victims of sexual violence in adolescents through literature review. This study uses a scoping review method through searches on the Pubmed database, EBSCOhost, and the Google Scholar search engine using the keywords "sexual violence victims", "teenagers, and coping strategies" in Indonesian and "adolescence", "coping strategies", and " victims of sexual violence” in English. The inclusion criteria for this research are articles that are relevant to the topic, full text, in Indonesian and English with a range of 2012-2022. The articles obtained and analyzed in this study were 9 articles. The results showed that the use of coping tended to vary, namely avoidance, creating positive meaning, controlling oneself, accepting, seeking support, planning, and confrontation. However, there are teenagers who use negative coping, namely by releasing problems, blaming themselves, and endangering themselves. The most widely used type of adolescent coping strategy is emotion-focused coping. Many factors influence the coping strategies of victims of sexual violence in adolescents, one of which is social support. This research is expected to be a consideration for nurses and families of victims to pay more attention to adolescent coping strategies, especially for victims of sexual violence.Abstrak: Kekerasan seksual yang terjadi pada usia remaja dapat mempengaruhi perkembangannya dalam berbagai aspek di kehidupan. Situasi stres yang dialami korban berdampak pada fisiologis, psikologis, dan sosial. Individu akan melakukan koping untuk mengatasinya. Remaja seringkali terjerumus dalam strategi koping yang maladaptif sehingga menyebabkan remaja mengalami depresi. Penelitian ini bertujuan untuk mengidentifikasi strategi koping korban kekerasan seksual pada remaja melalui kajian literatur. Penelitian ini menggunakanmetode scoping review melalui pencarian pada database Pubmed, EBSCOhost, serta search engine Google Scholar menggunakan kata kunci “korban kekerasan seksual”, “remaja, dan strategi koping” dalam bahasa Indonesia dan “adolescence” , “coping strategies”,  dan “victims of sexual violence” dalam bahasa Inggris. Kriteria Inklusi penelitian ini yaitu artikel yang relevan dengan topik, full text, berbahasa Indonesia maupun Inggris dengan rentang tahun 2012-2022. Artikel yang didapat dan dianalisis dalam penelitian ini adalah sebanyak 9 artikel. Hasil penelitian menunjukan bahwa penggunaan koping cenderung bervariasi yakni melakukan penghindaran, menciptakan makna positif, mengontrol diri, menerima, mencari dukungan, perencanaan, dan konfrontatif. Namun, terdapat remaja yag meggunakan kopig negatif yaitu dengan pelepasan masalah, menyalahkan diri, dan membahayakan diri. Jenis strategi koping remaja yang paling banyak digunakan ialah emotion-focused coping. Banyak faktor yang memengaruhi strategi koping korban kekerasan seksual pada remaja salah satunya yaitu dukungan sosial. Penelitian ini diharapkan menjadi pertimbangan bagi perawat dan keluarga korban agar lebih memperhatikan strategi koping remaja khususnya pada korban kekerasan seksual.